Analisis Komparasi Profitabilitas Pertanian Padi Organik dan Anorganik di Desa Lombok Kulon Kabupaten Bondowoso - Yeremia von Savigny; Hari Sukarno; Novi Puspitasari (Universitas Jember, 2019)
Profitability is a very important element for a business or company. Profitability ratios are usually used to see how the effectiveness and efficiency of a business in the use of venture capital. The factors that affect the level of profitability in this study are the cost of production, production, sales and profits. This research discusses how to compare the profitability of organic and inorganic rice farming. The analysis was conducted on 13 samples of organic rice farmers and 30 samples of inorganic farmers domiciled in Lombok Kulon Village, Bondowoso Regency. This study uses two types of profitability, namely Net Profit Margin (NPM) and Return On Capital Employed (ROCE). The test uses the Independent sample t-test and the Mann Whitney Test, depending on the results of the normality test data. The test results show that there are differences in the level of profitability of organic rice farming and inorganic rice farming. The test results with the statistical difference test also showed that there were significant differences in the comparison of the profitability levels in the two agricultural systems. Thus it can be concluded that there are significant differences in the level of profitability of Net Profit Margin (NPM) and Return On Capital Employed (ROCE) in organic and inorganic rice farming systems. Keywords: Profitability Ratio, NPM, ROCE, Organic Rice and AnOrganic Rice.